2000
DOI: 10.1136/heart.84.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of congenital heart disease in the northern region of England: benefits of a training programme for obstetric ultrasonographers

Abstract: Objective-To examine the results of fetal cardiac scanning and audit the changes in performance resulting from the introduction of a training programme for obstetric ultrasonographers. Methods-Using the database of the Northern Regional Congenital Abnormality Survey (NORCAS), fetuses with complex or significant congenital heart disease (CCHD) diagnosed prenatally in 1994 were identified. A simple programme of centralised and local training was instituted in 1995 by the department of paediatric cardiology to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 10 publications
8
115
0
6
Order By: Relevance
“…The recent significant decrease in the birth of babies with HLHS is an example for this situation (14). Hunter et al (8) found the termination rate in 1994 as 22.7% and in 1997 as 57%. Therefore, the prevalence of complex and serious CHD was reduced from 3.3/1000 live births to 2.6/1000 live births.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent significant decrease in the birth of babies with HLHS is an example for this situation (14). Hunter et al (8) found the termination rate in 1994 as 22.7% and in 1997 as 57%. Therefore, the prevalence of complex and serious CHD was reduced from 3.3/1000 live births to 2.6/1000 live births.…”
Section: Discussionmentioning
confidence: 99%
“…A modified classification system similar to that of Hunter et al (8) and Wren et al (9) was used in categorization of congenital heart defects ( Table 1). Category I included cardiac anomalies or groups of anomalies, which were inoperable, incompletely correctable or only managed with palliative care and classified as complex.…”
Section: Fetal Echocardiographic Examinationmentioning
confidence: 99%
“…Como ejemplo, la tasa de detección de defectos cardíacos mayores se duplicó luego de la implementación de un Programa de capacitación de 2 años en un centro médico en el norte de Inglaterra (47,48).…”
Section: Impacto De Los Programas De Detección Antenatalunclassified
“…As the teaching study from Hunter et al demonstrated, there is a danger that if support from paediatric cardiology is not ongoing then the initial efficacy of training may diminish. (Hunter et al, 2000) Telemedicine has the potential to facilitate earlier diagnosis of CHD by offering increased and quicker access to specialist opinion. Telemedicine may also support sonographers' education and training.…”
Section: The Clinical Imperativementioning
confidence: 99%